2015
DOI: 10.1097/aog.0000000000001088
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Disparities in Hysterectomy for Gynecologic Cancers

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…By generating multivariable models that adjusted for patient-level factors, we were able to expose the role of confounding on previously described associations between race and access to MIH. 4,[8][9][10][11] In the United States, we found that African American race, low income, and underinsurance are all associated with overweight and obesity. 13 Obesity limits the application of laparoscopic and robot-assisted surgery; obese women have greater odds of vaginal over other routes of hysterectomy.…”
Section: Commentmentioning
confidence: 74%
See 3 more Smart Citations
“…By generating multivariable models that adjusted for patient-level factors, we were able to expose the role of confounding on previously described associations between race and access to MIH. 4,[8][9][10][11] In the United States, we found that African American race, low income, and underinsurance are all associated with overweight and obesity. 13 Obesity limits the application of laparoscopic and robot-assisted surgery; obese women have greater odds of vaginal over other routes of hysterectomy.…”
Section: Commentmentioning
confidence: 74%
“…Being in the highest income quartile (compared to the lowest) and having private insurance (compared to Medicaid) also Previous analyses have shown racial and socioeconomic disparities in laparoscopic hysterectomy overall but most have not evaluated the role of robotassisted hysterectomy specifically, as national databases rarely differentiate between laparoscopic surgeries performed with and without robot assistance. 4,[8][9][10][11] In our subgroup analyses, adjusting for confounding in multivariable analysis did eliminate many univariate associations between In contrast to trends in robot-assisted hysterectomy, the odds of undergoing vaginal hysterectomy over abdominal hysterectomy were higher among women in the lowest income quartile compared to those in the highest income quartile and among African Americans compared to whites. Individual practice patterns and patient characteristics at the 3 hospitals could explain the findings noted despite having controlled for hospital itself.…”
Section: Commentmentioning
confidence: 82%
See 2 more Smart Citations
“…2 In the USA, women of color experience higher rates of severe maternal morbidity [3][4][5][6][7] and death during and after pregnancy. Although race/ ethnicity is known to be associated with disparate outcomes in nonobstetric hysterectomy care, 8,9 the relationship between race/ethnicity and peripartum hysterectomy 6,[10][11][12] or its related outcomes 10 is not well-explored. Recent publications focus on differences in outcomes after peripartum hysterectomy based on hospital characteristics, without examining disparities among minority groups, 13,14 or they have combined peripartum hysterectomy with other maternal morbidity outcomes.…”
Section: Introductionmentioning
confidence: 99%